2012
DOI: 10.1177/1403494812454233
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset smokers: How many, and associations with health behaviours and socioeconomic status

Abstract: Early adulthood is an additional critical phase for daily smoking initiation. The clear and consistent negative association between SES and late-onset smoking, as well as the positive association between SES and smoking cessation, contribute to the association between SES and smoking in the general adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
2
11
1
2
Order By: Relevance
“…The current study found limited impact of physical activity on the smoking-related disability risk after taking into account social confounding, which gives some support to studies that indicate a relation between physical activity and socioeconomic status 28 29. A previous study of the disability risk among the physically active and inactive smokers did not adjust for socioeconomic status, making comparisons with the present study difficult 2…”
Section: Discussionsupporting
confidence: 66%
“…The current study found limited impact of physical activity on the smoking-related disability risk after taking into account social confounding, which gives some support to studies that indicate a relation between physical activity and socioeconomic status 28 29. A previous study of the disability risk among the physically active and inactive smokers did not adjust for socioeconomic status, making comparisons with the present study difficult 2…”
Section: Discussionsupporting
confidence: 66%
“…21 This issue remains critically important in light of the deficient evidence on interventions able to reliably reduce smoking-related inequalities 22,23 and the widening of inequalities in smoking initiation over time. [24][25][26] Consistent with an increasing amount of research on young adult initiation, [10][11][12][13] we found that proportions of initiation made during young adulthood had not decreased in our retrospective cohorts between 2001 and 2013. This means that initiation during young adulthood also represented a progressively larger proportion of initiation behaviour, which is in stark contrast with the first reports to study this issue.…”
Section: Discussionsupporting
confidence: 66%
“…[7][8][9] Recent studies suggests that young adult smoking initiation rates in Canada and the US could be as high as 30%. [10][11][12][13] Of particular concern, certain reports suggest that young adult initiation rates might even be increasing for some groups. 5,13,14 For instance, Terry-McElrath and O'Malley found using large consecutive American young adult cohorts that initiation rates during young adulthood of experimental and occasional smoking increased almost twofold over the last three decades.…”
mentioning
confidence: 99%
“…1). Smoking behaviour is not static, and other studies using this same data set have highlighted the importance of late-onset smoking and quitting in both adolescence [28] and adulthood [29]. Indeed, the time-invariant smoking factor was weaker than the corresponding for depression, which indicates that smoking is less stable than depression over these nine data waves.…”
Section: Discussionmentioning
confidence: 81%